1851 The 'CREATE' project: creating the right environment for adolescents and team empowerment. (15th December 2022) - Modgil, Gita; Thomas, Neil; Kyle, Anna; McCann, Kate; Mason, Suzy; Mirams, Becky; Jackson, Caroline; Cooke, Laura; Whiting, Amy
Abstract : Objectives: The paediatric landscape for the care needs of young people is rapidly evolving. Traditional models of care pathways and team colleagues in our acute hospital settings need to advance at pace. Colleagues have come together locally to reflect upon shared experiences & to co-produce ideas about how to 'CREATE': Create the Right Environment for Adolescents & Team colleagues, to Empower teams caring for young people on our children's unit. Methods: Following complex cases on our acute unit, a joint reflective open session was held in September 2021 with paediatrics, CAMHS, lead nurses, medical directors, chief medical officers, occupational therapists, head of resilience/training, social workers, psychologist, physiotherapists, playteams, security and mental health nurses. The huge response clearly demonstrated the desire to influence productive, supportive change for our environment and to explore how best to support distressed young people. The CREATE team was born: 'an umbrella concept' representing a multidisciplinary group leading change for the young person's voice, training, supporting colleagues, culture, our clinical care and physical environment. Results: The CREATE workstreams include: 1. Clinical Care/Young Person & Family Experience: Individualised daily care plans; optimising care introducing ' tell it once' and ' this is me' documents; exploring nurse led HEADSSS screening (identifying risk of trauma/adverse childhood experiences); identifying young persons advocate; exploring ' therapeutic education' . 2. Workforce planning: Successfully leading business cases for expansion of children and young people social, emotional and mental health nurse team; band 3 nursing support; youth worker; occupational therapist; activities co-ordinator; consultant (specialist interest in adolescent health). 3. Engagement/Culture: Capturing colleague experience: ' Your Voice - Behaviours that challenge' : powerful feedback created collaborative improvements; reframing language used; recognition of re-traumatisation for young person/colleagues; continued development of monthly 'drop -in'/safe space for MDT to share feelings with CAMHS staff regarding complex/traumatising cases. 4. Environmental Improvements: Children & Young People National Survey results used to create a 'sanctuary space' for young people on the acute unit, utilising local funding bids in liaison with 'Arts For Life' and co-production from young people/colleagues. 5. Training/Education/Quality Improvement: Recognition of trauma informed care underpinning experience/training with the development of a generic module and specific multi-disciplinary simulation situation learning; trauma informed workstream created to support the trust strategy process; The 'We Can Talk' QI project has been rolled out across whole acute trust to develop and implement ' Emotional Observations ' for those aged 12–18 years old in acute services, in order to imbed parity of esteem within practice for all children/young people. Conclusions: The CREATE project has developed over 10 months and demonstrates what can be successfully be achieved with listening to the voices of colleagues and experiences of children and young people on our acute unit, alongside the desire for change to meet the evolving and sometimes complex needs of young people presenting to an acute hospital setting. Further development is in progress including the concept of true co-production of this project, understanding and changing the landscape for restorative clinical and managerial supervision for acute colleagues in line with mental health colleagues.